Biobank Participants' Attitudes Toward Data Sharing and Privacy: The Role of Trust in Reducing Perceived Risks. (February 2022) - Kasperbauer, T.J.; Halverson, Colin; Garcia, Abby; Schwartz, Peter H.
Biobank participants are often unaware of possible uses of their genetic and health information, despite explicit descriptions of those uses in consent forms. To explore why this misunderstanding persists, we conducted semi-structured interviews and knowledge tests with 22 participants who had recently enrolled in a research biobank. Results indicated that participants lacked understanding of privacy and data-sharing topics but were mostly unconcerned about associated risks. Participants described their answers on the knowledge test as largely driven by their trust in the healthcare system, not by a close reading of the information presented to them. This finding may help explain the difficulties in increasing participant understanding of privacy-related topics, even when such information is clearly presented in biobank consent forms.